Editorial - Vosloo, Robert (Stellenbosch theological journal, 2022)
In this 2022 edition of the Stellenbosch Theological Journal (STJ) we are proud to present 40 peer-reviewed academic articles and 6 book reviews. Ten of these articles (STJ Vol. 8 No. 2) are published in the section of the "Society of Practical Theology in South Africa (SPTSA; with Anita Cloete as managing editor).